Decoding the Anticancer Mechanism of Action of Kaempferol in Liver Cancer Cells via Transcriptomics, Network Pharmacology, Molecular Docking, Dynamics Simulations, and in vitro Validation - He, Zhen; Liu, Wei; Liu, Wei; Xing, Guoqiang (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Kaempferol, a dietary flavonoid with proven antioxidant and antiinflammatory properties, has garnered significant interest in cancer research for its ability to modulate multiple oncogenic pathways, making it a compelling candidate for multitargeted therapy in addressing the considerable health burden of liver cancer. Objectives: To elucidate the therapeutic potential of kaempferol through network pharmacology, and in vitro experimental methodology. Materials and Methods: The pharmacological and physico-chemical properties of kaempferol were assessed using SwissADME and Protox-3.0. Target prediction utilized SuperPred and SwissTargetPrediction, filtered for liver cancer-specific genes through GeneCards. Protein-Protein Interaction (PPI) networks were constructed in Cytoscape, with hub genes identified via cytoHubba. Functional enrichment analyses, molecular docking, and dynamics were conducted, supported by GEPIA2 and TIMER analyses. HEP-G2 cell assays evaluated cell cytotoxicity, cell migration, apoptosis, and cell cycle phase distribution effects. Results: Kaempferol exhibited favorable drug-likeness, low toxicity, and potent interactions with liver cancer targets. Hub genes (GSK3B, MMP9, STAT1) were identified, linked to key cancer pathways (Wnt, PI3K-Akt, ECM-receptor). Molecular docking demonstrated high affinity for GSK3B (-8.9 kcal/mol), MMP9 (-9.2 kcal/mol), and STAT1 (-7 kcal/mol), with stable interactions validated by dynamics. Expression analyses revealed upregulation of these genes in liver cancer, correlated with immune infiltration patterns. Experimentally, kaempferol reduced HEP-G2 cell viability in a dose-dependent manner, significantly inhibited cell migration, induced cell apoptosis (early and late), and arrested cells at the G2/M phase. Conclusion: Kaempferol regulates critical pathways in liver cancer, exhibiting potent anticancer effects through induction of apoptosis, inhibition of cell migration, and cell cycle arrest, thereby positioning it as a compelling prospect for therapeutic development.
Keywords: Natural Products; Bioinformatics; Network Pharmacology; Liver cancer; Molecular; Docking; Apoptosis